Implementasi Kebijakan Kota Layak Anak (KLA) di Kelurahan Bende Kecamatan Kadia Kota Kendari - La Ode Wahiyuddin; Muhammad Ihsan Mattalitti; Darwan Sari; Isman Isman (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2023)
This research describes the implementation of the KLA policy in the Bende sub-district, Kadia sub-district, Kendari city. Describe the implementation of KLA policy in the Bende sub-district based on four factors in implementing public policy. The research method used is a qualitative descriptive research method with data collection through interviews, observation, and documentation. The results of the data collection will be presented descriptively. The results of research conducted were based on 4 factors that influence KLA policy, including: 1) KLA policy outreach and campaign activities in Bende sub-district are still not carried out so that many people still don't know about KLA policy due to the Covid-19 outbreak which also hit Kendari City so that the budget socialization activities and KLA policy campaigns in the Bende sub-district were diverted; 2) None of the GT KLA members of Bende subdistrict have trained on children's rights, although GT KLA members of Bende subdistrict have shown a fairly high level of concern for educating children's rights, but GT KLA members must know and understand the substance of KLA policies; 3) GT KLA members and the Bende sub-district community show an attitude that supports KLA policies, making it easier to implement KLA policies; 4) The institutional structure of GT KLA, Bede sub-district is quite good because it is filled with capable personnel and resources who have qualifications that are appropriate to the fields involving children's rights. These fields have the duties and functions to prepare and carry out activities in the context of implementing KLA policies in the Bende sub-district. The conclusion of the results of this study is that the implementation of the KLA policy in the Bede village is still not optimal. Suggestions that can be given are the need for outreach and campaign activities for the community and child rights training for GT KLA members in the Bende sub-district. Apart from that, facilities supporting the implementation of KLA policies also need to be improved, one of which can be through social responsibility, private parties such as the business world and mass media as well as strengthening the GT KLA institution through SOP indicators or standards for implementing KLA policies in the Bende sub-district.